COMPLETE MISCIBILITY BETWEEN SILICATE MELTS AND HYDROUS FLUIDS IN THE UPPER MANTLE: EXPERIMENTAL EVIDENCE AND GEOCHEMICAL IMPLICATIONS - Bureau H.; Keppler H. (My University, 1999)
The phase relationships between silicate melts and hydrous fluids were studied by direct visual observation in an externally heated diamond-anvil cell. Complete miscibility of silicate melt and water was observed for a wide range of melt compositions, including nepheline, jadeite, dacite, haplogranite and Ca-bearing granite. Some evidence for complete miscibility was also observed in the system basalt–H2O. The critical temperatures in all systems decrease rapidly with pressure. At 15 kbar, the critical temperature for nepheline is around 550°C, for jadeite around 800°C and for granitic compositions it is close to 900°C. In general, the critical temperatures appear to increase with silica content in the system. Our results suggest that there is complete miscibility between silicate melts and water in most of the upper mantle, except at very shallow depths. This means that a water-saturated solidus cannot be defined any more in the deeper parts of the upper mantle. Very silica-rich melt inclusions found in spinel lherzolites associated with fluid inclusion are probably the result of the unmixing of a supercritical fluid containing comparable amounts of water and silicate components. The decomposition of amphibole in a subducted slab occurs at conditions where the miscibility gap between fluid and silicate melt is not yet closed, while the decomposition of phengite and lawsonite occurs far beyond the critical curve. Accordingly, the fluids released by the breakdown of these minerals should have very different properties. Highly mobile, hydrous fluids containing little dissolved silicate should be produced by amphibole breakdown, while the decomposition of lawsonite and phengite will lead to much more silicate-rich and less mobile fluid phases.